ECONOMIC TRANSFORMATION OF THE COMPETITIVE POTENTIAL OF THE TOURISM INDUSTRY SUBJECTS: METHODOLOGICAL CONCEPT - Ierko, Iryna; Demianchuk, Olena; Golub, Gennadii; Pohrebskyi, Taras; Gazuda, Sergij; Vashchuk, Liudmyla (Fìnansovo-kreditna dìâlʹnìstʹ: problemi teorìì̈ ta praktiki (Online), 2023)
The article considers the methodological concept of economic transformation of the competitive potential of the tourism industry subjects and characterizes the elements of it. The focus is on the stages (phases) of economic transformation of the competitive potential of the tourism industry. The study reveals consistent and regular changes in its development, from turbulence to transformation. Transformation is a long-term process that brings drastic qualitative and quantitative changes to the economy. The principles that govern the economic transformation of the competitive potential of the tourism industry subjects include objectivity, historicism, systematicity, consumer value, reproduction, and smart specialization. The basis of the economic transformational process is a modification of the criteria for evaluating the competitive advantages of the subjects, namely the sustainability, safety, and competitive advantages. Approaches to developing a tourism subject's competitive potential in the post-war period in Ukraine are analyzed. They determine the interdependencies of economic transformation processes, the dynamics of their course, and evolutionary changes (transformation cycle). The economic transformation tools are identified. They depend on transformational changes and require well-considered means and management measures when changing the old model into a new one, which influences the rapidness of changes. The model involves a scheme for evaluating the economic transformational processes using three main criteria of assessment: sustainability, safety, and the competitive advantages of the tourism industry subject. The article presents several scenarios for implementing the model of economic transformation of the competitive potential of the tourism industry entity, describing them as inertial, pessimistic, optimistic, and realistic. Depending on the scenario, a differentiated approach to a mechanism and the corresponding institutional infrastructure for economic transformation of the competitive potential of tourism industry entities are developed. The research findings indicate that the highlighted methodological concept can ensure a high level of development of competitive potential for tourism industry entities.